Evaluating the Ability to Achieve Efficiency in Providing Services of the Freight Forwarding Firms in Viet Nam - Nguyen, Linh Tran Cam; Nga, Duong Quynh; Trang, Pham Ng?c Thu (International Journal of Supply Chain Management, 2019)
In recent years, Vietnam freight forwarding industry is growing and contributing significantly to the national GDP. However, the efficiency in providing service delivery at the domestic firms is not high to compete with multinational companies that are strong potential and finance. There have been many studies on freight forwarding, but mainly qualitative research and other studies are in-depth analysis logistics. This research presents the factors that affect efficiency in providing services. This research has been used factor analysis method and binary regression model (Binary Logistics) and identified 4 factors that affect the efficiency in providing service of freight forwarding firms: (1) Resources of business (2) Outcomes (3) The quality of staffs (4) The relationship between enterprises and their customers, and outcomes is the factor provided the highest positive correlation to the ability to achieve efficiency in providing services of freight forwarding firms.Binary Logistic model showed the probability of business efficiency is 72.5%. Thus, at the level of resources to provide services is 3.35, the outcome is 3.66, quality of the staffs is 3.59 and the relationship with customers is 3.40, shows that enterprises operate efficiently. Value prediction accuracy of the model is 93.3%.